Physics in the mesosphere/lower thermosphere: A personal perspective - Lübken, Franz-Josef (Frontiers in Astronomy and Space Sciences, 2022)
The scope of this paper is to present some progress being made in the last few decades regarding some aspects of physical processes in the mesosphere/lower thermosphere and to point to some open questions. This summary is presented from a personal perspective, i.e., this is not a review of a certain science topic. Most citations reflect my own work or are representative examples only. They are not meant to be complete or comprehensive.